geoSDI ERA: gestire le emergenze in maniera integrata e condivisa - Dello Buono, Dimitri (GEOmedia, 2009)
geoSDI: integrated and shared emergencies managing GeoSDI is a programme coordinated by the Italian Department for Civil Protection, aimed to the design and development of the Italian National Spatial Data Infrastructure, according to the provisions of the INSPIRE Directive, using open source software applications. The GeoSDI Framework follows the OGC Standards and is therefore compatible and interoperable with other SDI tools possibly being used by other Civil Protection actors in the Mediterranean region. The web application GeoSDI ERA (at the top of the logical geoSDI framework stack) allows to manage collaboratively a system of open access web servers and to use their interoperable information services for creating personalised maps with multiple layers of information, sharing the maps with other users, aggregating and analysing information.GeoSDI ERA is succesfully being used during the emergency activities of recent eartquake in Abruzzo.dati